Photonic Therapeutics and Diagnostics III 2007
DOI: 10.1117/12.702411
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton tomography of skin tumors after ALA application

Abstract: In skin, the most common form of cancer is the basal cell carcinoma, affecting about 800.000 people in US each year. One of the treatments is photodynamic therapy (PDT) with a topical application of 5-aminolevulinic acid (ALA) derivates. These photosensitizers accumulate mainly in cancerous cells and can be activated by light resulting in a destruction of the cells. We performed multiphoton tomography based on near-infrared (NIR) femtosecond laser pulses on skin biopsies in order to study the biosynthesis of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…using fluorescence excitation in the range of 750–800 nm [11, 15], did not reveal any specific fluorescence signal from PpIX. Therefore, a detailed study of the excitation and emission of endogenously formed PpIX was undertaken.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…using fluorescence excitation in the range of 750–800 nm [11, 15], did not reveal any specific fluorescence signal from PpIX. Therefore, a detailed study of the excitation and emission of endogenously formed PpIX was undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary data exist, but reports are mainly restricted to cell cultures [1215]. Data from skin tumors are limited and lack thorough spectral investigations [11, 15]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most studies using PpIX fluorescence for MPT-FLIM imaging are limited to cell cultures [98, 99] and solutions [100]. Riemann et al [101] used MPT on skin biopsies to study the biosynthesis of PpIX and also to evaluate the therapy. Cicchi et al [102] demonstrated enhanced tumor contrast and depth of imaging by using MAL-induced PpIX as the contrast agent, and two-photon excitation (TPE) in combination with FLIM as the imaging technique.…”
Section: Approaches For Measuring Ppix Beneath the Surface Of The Skinmentioning
confidence: 99%
“…One also may gain information about the state of tissues themselves like determining irregularities leading to diagnosis of abnormal parts. The examination of the reaction of skin cells to UV irradiation as well as of pigmented skin cells and segments like nevi may help to investigate photo induced processes and disorders [12][13][14][15][16][17][18][19] . In ageing processes and certain diseases of skin certain changes of the collagen and elastin content of the dermis could be observed.…”
Section: Introductionmentioning
confidence: 99%